Locoregional Control and Survival in Children, Adolescents, and Young Adults With Localized Head and Neck Alveolar Rhabdomyosarcoma—The French Experience - Machavoine, Roxane; Helfre, Sylvie; Bernier, Valérie; Bolle, Stéphanie; Leseur, Julie; Corradini, Nadège; Rome, Angélique; Defachelles, Anne-Sophie; Deneuve, Sophie; Bernard, Sophie; Fayoux, Pierre; Nicollas, Richard; et al. (Frontiers in Pediatrics, 2022)
Introduction The head and neck (HN) are the most frequent sites of pediatric rhabdomyosarcoma (RMS). Alveolar RMS (ARMS) represents ~20% of all RMS cases and frequently spread to lymph nodes (LNs). The aim was to report locoregional control, event-free survival (EFS), and overall survival (OS), according to clinical and pathological features, LN staging, and treatment modalities. Methods The study included all patients prospectively enrolled in EpSSG RMS 2005 study under 21 years of age with localized HN ARMS and diagnosed between 2005 and 2016 in France. Medical data including imaging, surgical report, and radiation therapy planes were analyzed. Results Forty-eight patients (median age 6 years; range 4 months−21 years), corresponding to 30 parameningeal and 18 non-parameningeal ARMS, were included. There were 33 boys (69%). Tumor locations included the following: orbit (n = 7) among which four cases had bone erosion, paranasal sinuses and nasal cavity (n = 16), deep facial spaces (n = 10), nasolabial fold (n = 8), and other non-parameningeal HN sites (n = 7). A fusion transcript of PAX3-FOXO1 or PAX7-FOXO1 was expressed in 33 of the 45 cases (73%) with molecular analysis. At diagnosis, 10 patients had primary resection of the primary tumor (PRPT) (none with microscopic complete resection) and 9 had LN staging. After induction chemotherapy, 26 patients (54%) had secondary resection of the primary tumor (SRPT) and 13 patients (27%) had cervical LN dissection. A total of 43 patients (90%) were treated with radiation therapy. With a median follow-up of 7 years (range 2–13 years), 5-year OS and EFS were 78% (95% CI, 63–88%) and 66% (95% CI, 51–78%), respectively. We observed 16 events (10 deaths): 4 local, 4 regional, 1 local and regional, and 7 metastatic. In univariate analysis, OS was only superior for patients under 10 years of age (p = 0.002), while FOXO1-negative ARMS, SRPT for parameningeal ARMS, and LN surgery were associated with significantly better EFS. Conclusion Our study confirms a better outcome for fusion-negative ARMS and ARMS in children under 10 years. Moreover, LN surgery and SRPT of parameningeal tumor may improve EFS of ARMS. Larger studies are needed to confirm our findings.